Cultural Values as Approach to Forming an Attitude of Religious Tolerance: Legal Politics of the Right to Religious Freedom - Fatma, Fatma; Saleh Ridwan, Muhammad; Shuhufi, Muhammad (Journal of Law, Politic and Humanities, 2023)
Religious intolerance has entered an emergency phase both globally and nationally. Overcoming religious intolerance as an effort to fulfill the right to freedom of religion continues to seek the right formulation with various alternative approaches that are easily accepted by society. This article aims to provide a basic understanding of the formation of official state policies through a cultural values approach that includes values of religious tolerance in Indonesia, especially cultural values of the Bugis and Toraja tribes groups in South Sulawesi Province, Indonesia. The method used is normative legal research with historical and statutory approaches, studying secondary data consisting of primary and secondary legal materials. Data were analyzed descriptively and prescriptively. The results of the study show that in Indonesia, South Sulawesi Province, especially the Bugis and Toraja tribes, there are cultural values that contain the value of religious tolerance. In the Bugis ethnic group, there are cultural values of Siri' Na Pesse and Assimareng which mean mutual cooperation, mutual respect, and respect regardless of socio-religious status, strong solidarity, and empathy for the suffering of others. Furthermore, the value of tolerance for the Toraja tribe is contained in the Longko and Pasomba Tedong values, which mean feeling grateful by blessing and respecting each other, tolerance is expressed in good speech, body language, perspective of others, and not embarrassing other people on the grounds of religious differences, the Toraja tribes believe that looking down on others is the same as embarrassing yourself.